'It's a plus rather than a must': perspectives of mainstream teachers in China on the influence of advertised educational ethos in supplementary English education. Issue 6 (18th August 2021) - Luo, Jiahui; Forbes, Karen
ABSTRACT: The recent upsurge of supplementary education has brought something attention-grabbing to the mediascape in China – educational ethos, inclusive of pedagogies and teaching ideals, is being widely marketed and increasingly used as a benchmark of 'quality' in education. This study explores the ways in which educational ethos in China is advertised by companies providing supplementary English education for elementary school students (SEEE), and investigates how mainstream teachers perceive the influence of the ethos on mainstream schooling. Ethos was first mapped out through investigation of 10 leading SEEE companies' websites, and 6 mainstream teachers were subsequently interviewed. A schematic paradigm was created to capture advertised ethos which indicates bottom-up educational development towards more interactive and practical English education in China. Interview findings identify three key levels of influence on mainstream schooling: (1) institutional, including accelerating pedagogical reforms; (2) interpersonal, such as increasing teacher–parent tension, and; (3) individual views on language education.